8 - Access to Higher Education during the Covid-19 Pandemic: What Mitigations Can be Made for the Future of African Higher Education - Mtawa, Ntimi; Fongwa, Samuel; Wangenge-Ouma , Gerald; Munene, Ishmael; Kibona, Bertha (CODESRIA Bulletin, 2023)